Prevalence of Unhealthy Lifestyle Among Health Science Students in Ajman, UAE: A Cross-Sectional Study - Shakir, Mohammad; Razack, Jafrin Sadiq Abdul; Sainul, Ajimal; Cherian, Noel George; Ossanam, Antony Calvin; Abubacker Musthafa, Hisham (International Journal of Innovative Research in Medical Science, 2025)
Objectives: This study aimed to assess the prevalence of unhealthy lifestyle behaviors (sleep, diet, physical activity, and smoking) among health science students in Ajman, UAE, and explore associations with sociodemographic factors (age, gender, nationality). Methods: This is a descriptive cross-sectional quantitative study involving health science students aged 18-25. Data collection started after obtaining permission to conduct the study, an IRB, and official approval from the sites. The goal was to deliver questionnaires to suitable participants who agreed to participate and signed the consent form. The information obtained from those questionnaires was organized and arranged in SPSS and Excel. Results: In our study, in terms of sleep habits, it was found that 65.9% were unhealthy; Dietary habits, it was found that 74.55% were unhealthy; Physical exercise, it was found that 70.7% were unhealthy; Smoking, it was found that 23.8% were unhealthy. Conclusions: The prevalence of unhealthy lifestyles in our study is notably higher compared to other studies. Significant findings include associations between diet quality and both age and program type, fruit and vegetable intake and program type, milk intake and nationality, physical exercise status and duration with gender, and smoking status with both gender and nationality.